\(\frac{\sqrt{35}+\sqrt{14}}{\sqrt{2}+\sqrt...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 7 2021

\(\frac{\sqrt{35}+\sqrt{14}}{\sqrt{2}+\sqrt{5}}-\frac{2\sqrt{21}-\sqrt{56}}{\sqrt{3}-\sqrt{2}}\)

\(\frac{\sqrt{7}\left(\sqrt{5}+\sqrt{2}\right)}{\sqrt{2}+\sqrt{5}}-\frac{2\sqrt{7}\left(\sqrt{3}-\sqrt{2}\right)}{\sqrt{3}-\sqrt{2}}\)

\(=\sqrt{7}-2\sqrt{7}\)

\(=-\sqrt{7}\)

7 tháng 6 2019

Thêm câu này hộ tớ nx nhé !
e) \(\left(\sqrt{8}-3\sqrt{2}+\sqrt{10}\right).\left(\sqrt{2}-3\sqrt{0.4}\right)\)

14 tháng 7 2019

\(a,\left(\frac{2\sqrt{3}-\sqrt{6}}{\sqrt{8}-2}-\frac{\sqrt{216}}{3}\right)\cdot\frac{1}{\sqrt{6}}\)

\(=\left(\frac{\sqrt{12}-\sqrt{6}}{2\left(\sqrt{2}-1\right)}-\frac{6\sqrt{6}}{3}\right)\cdot\frac{1}{\sqrt{6}}\)

\(=\left(\frac{\sqrt{6}\left(\sqrt{2}-1\right)}{2\left(\sqrt{2}-1\right)}-2\sqrt{6}\right)\cdot\frac{1}{\sqrt{6}}\)

\(=\left(\frac{\sqrt{6}}{2}-\frac{4\sqrt{6}}{2}\right)\cdot\frac{1}{\sqrt{6}}\)

\(=\frac{\sqrt{6}-4\sqrt{6}}{2}\cdot\frac{1}{\sqrt{6}}\)

\(=\frac{-3\sqrt{6}}{2}\cdot\frac{1}{\sqrt{6}}\)

\(=-\frac{3}{2}\)

6 tháng 8 2018

\(\frac{2\sqrt{12}-\sqrt{6}}{2\sqrt{6}-\sqrt{3}}+\frac{10+\sqrt{5}}{2\sqrt{15}+\sqrt{3}}\)

\(=\frac{\sqrt{2}\left(2\sqrt{6}-\sqrt{3}\right)}{2\sqrt{6}-\sqrt{3}}+\frac{\sqrt{5}\left(2\sqrt{5}+1\right)}{\sqrt{3}\left(2\sqrt{5}+1\right)}\)

\(=\sqrt{2}+\frac{\sqrt{5}}{\sqrt{3}}\)

\(=\frac{\sqrt{6}+\sqrt{5}}{\sqrt{3}}\)

p/s: chúc bạn học tốt

6 tháng 8 2018

\(\left(\frac{3+2\sqrt{3}}{\sqrt{3}+2}+\frac{2+\sqrt{2}}{\sqrt{2}+1}\right):\left(\sqrt{2}+\sqrt{3}\right)\)

\(=\left(\frac{\sqrt{3}\left(\sqrt{3}+2\right)}{\sqrt{3}+2}+\frac{\sqrt{2}\left(\sqrt{2}+1\right)}{\sqrt{2}+1}\right):\left(\sqrt{2}+\sqrt{3}\right)\)

\(=\left(\sqrt{3}+\sqrt{2}\right):\left(\sqrt{2}+\sqrt{3}\right)\)

\(=1\)

p/s: chúc bạn học tốt

5 tháng 10 2020

a) \(A=\frac{1}{2}\sqrt{32}+\sqrt{98}-\frac{1}{6}\sqrt{18}=\frac{1}{2}\sqrt{4^2.2}+\sqrt{7^2.2}-\frac{1}{6}.\sqrt{3^2.2}\)

\(=\frac{1}{2}\sqrt{4^2}.\sqrt{2}+\sqrt{7^2}.\sqrt{2}-\frac{1}{6}.\sqrt{3^2}.\sqrt{2}\)\(=\frac{1}{2}.4\sqrt{2}+7\sqrt{2}-\frac{1}{6}.3.\sqrt{2}\)\(=2.\sqrt{2}+7\sqrt{2}-\frac{1}{2}\sqrt{2}=\left(2+7-\frac{1}{2}\right)\sqrt{2}=\frac{17}{2}\sqrt{2}\)

4 tháng 8 2020

Bài 1 :

\(6xy\cdot\sqrt{\frac{9x^2}{16y^2}}=6xy\cdot\frac{3x}{4y}=\frac{18x^2y}{4y}=\frac{9}{2}x^2\)

\(\sqrt{\frac{4+20a+25a^2}{b^4}}=\sqrt{\frac{\left(2+5a\right)^2}{\left(b^2\right)^2}}=\frac{2+5a}{b^2}\)

\(\left(m-n\right).\sqrt{\frac{m-n}{\left(m-n\right)^2}}=\sqrt{\left(m-n\right)^2}\cdot\sqrt{\frac{1}{m-n}}=\sqrt{\frac{\left(m-n\right)^2}{m-n}}=\sqrt{m-n}\)

Bài 2 : 

1. \(\left(2\sqrt{3}-\sqrt{12}\right):5\sqrt{3}=\left(2\sqrt{3}-2\sqrt{3}\right):5\sqrt{3}=0:5\sqrt{3}=0\)

2. \(\sqrt{\frac{317^2-302^2}{1013^2-1012^2}}=\frac{\sqrt{\left(317+302\right)\left(317-302\right)}}{\sqrt{\left(1013+1012\right)\left(1013-1012\right)}}=\frac{\sqrt{619}\cdot\sqrt{15}}{\sqrt{2025}}=\sqrt{\frac{619}{135}}\)(check lại)

3. \(\sqrt{27\left(1-\sqrt{3}\right)^2}:3\sqrt{75}\)

\(=\sqrt{27}\left(1-\sqrt{3}\right):15\sqrt{3}\)

\(=3\sqrt{3}\left(1-\sqrt{3}\right):15\sqrt{3}\)

\(=\frac{1-\sqrt{3}}{5}\)

4.\(\left(5\sqrt{\frac{1}{5}}+\frac{1}{2}\sqrt{20}-\frac{5}{4}\sqrt{\frac{4}{5}}+\sqrt{5}\right):2\sqrt{5}\)

\(=\left(\frac{5}{\sqrt{5}}+\frac{\sqrt{20}}{2}-\frac{\frac{5}{4}\cdot2}{\sqrt{5}}+\sqrt{5}\right):2\sqrt{5}\)

\(=\left(\sqrt{5}+\frac{2\sqrt{5}}{2}-\frac{\frac{5}{2}}{\sqrt{5}}+\sqrt{5}\right):2\sqrt{5}\)

\(=\left(\sqrt{5}+\sqrt{5}+\frac{\sqrt{5}}{2}+\sqrt{5}\right):2\sqrt{5}\)

\(=\frac{7}{2}\sqrt{5}:2\sqrt{5}\)

\(=\frac{7}{4}\)

5 tháng 8 2018

\(\sqrt{10-4\sqrt{6}}+\sqrt{33-12\sqrt{6}}\)

 \(=\sqrt{2^2-2.2.\sqrt{6}+\left(\sqrt{6}\right)^2}+\sqrt{3^2-2.3.2\sqrt{6}+\left(2\sqrt{6}\right)^2}\)

\(=\sqrt{\left(2-\sqrt{6}\right)^2}+\sqrt{\left(3-2\sqrt{6}\right)^2}\)

\(=-\left(2-\sqrt{6}\right)-\left(3-2\sqrt{6}\right)\)

\(=-2+\sqrt{6}-3+2\sqrt{6}\)

\(=-5+3\sqrt{6}\)

5 tháng 8 2018

\(\sqrt{16-6\sqrt{7}}+\sqrt{32-8\sqrt{7}}\)

\(=\sqrt{3^2-2.3.\sqrt{7}+\left(\sqrt{7}\right)^2}+\sqrt{2^2-2.2.2\sqrt{7}+\left(2\sqrt{7}\right)^2}\)

\(=\sqrt{\left(3-\sqrt{7}\right)^2}+\sqrt{\left(2-2\sqrt{7}\right)^2}\)

\(=3-\sqrt{7}-\left(2-2\sqrt{7}\right)\)

\(=3-\sqrt{7}-2+2\sqrt{7}\)

\(=1+\sqrt{7}\)